A simple model for control of tumor cells - Margarit, David Hipólito (2015)
The Kirschner-Panetta model describes the poblational competition between effector cells and tumor cells. We analize external changes in the parameters and mechanisms to obtain the decreasing of tumor cells. These variations were performed by three different ways: Oscillations, spikes with the natural frequency of the system, and spikes with Normal Distribution. It was observed that the amount of tumor cells decreases to zero if we change simultaneously the parameters properly.